The Implementation of Moodle Assistant Discovery Learning Model to Improve Writing Skills at SMK N 1 Ponjong - Endang Sugiharyanti; Alief Noor Farida; Sulistiyani (SEAMEO QITEP in Language, 2022)
This study aims to improve students’ application letter writing skills which are guided by the application of the Moodle-assisted Discovery Learning model. This research is a Classroom Action Research (CAR) with the object of research being the students of class XII TKR A SMK Negeri 1 Ponjong. The research was carried out in 2 cycles, starting from planning, implementing, observing, reflecting, and revising. The results showed that learning with the application of the Moodle-assisted Discovery Learning model worked better. This is evidenced by the increase in English Application Letter writing skills, seen from the percentage of students’ writing skills completeness that continually increases from the initial recorded value data of 57%. In the first cycle, it reached 79% and in the second cycle, it reached 94%. This means that there is a significant increase in the initial student achievement, to the first cycle, from the first cycle to the second cycle. so that the research was declared successful as shown by the increase in student achievement.